Electrocardiographic QRS duration is influenced by body mass index and sex. (December 2021) - Rao, Anupam C.A.; Ng, Austin C.C.; Sy, Raymond W.; Chia, Karin K.M.; Hansen, Peter S.; Chiha, Joseph; Kilian, Jens; Kanagaratnam, Logan B.
Highlights: In a large group of subjects without overt conduction system disease, there was a positive association between increasing BMI and electrocardiographic QRS duration that was independent of other covariates such as sex and age. Females had narrower QRS complex than the males at similar age and in the similar BMI category. Findings of this research should prompt further studies to explore the underlying mechanisms for these observations and potential reversibility of the conduction abnormality with weight loss Abstract: Background: Electrocardiogram (ECG) measured QRS duration has been shown to influence cardiovascular outcomes. However, there is paucity of data on whether ECG QRS duration is influenced by obesity and sex in large populations. Methods: All ECGs performed by a pathology provider over a 2-year period were included. ECGs with confounding factors and those not in sinus rhythm were excluded from the primary analysis. Results: Of the 76, 220 who met the inclusion criteria, 41, 685 (55%) were females. The median age of the study cohort was 61 years (interquartile [IQR] range 48–71 years). The median QRS duration was 86 ms (IQR 80–94 ms). The median BMI was 27.6 kg/m 2 (IQR 24.2–31.8 kg/m 2 ). When stratified according to the World Health Organization classification of BMI < 18.50 kg/m 2, 18.50–24.99 kg/m 2, 25.00–29.99 kg/m 2, and ≥ 30.00 kg/m 2, the median QRS durations were 82 ms (IQR 76–88 ms), 86 ms (IQR 80–92 ms), 88 ms (IQR 80–94 ms) and 88 ms (IQR 82–94 ms), respectively (p < 0.001 for linear trend). Median QRS duration for females was 84 ms (IQR 78–88 ms); for males, it was 92 ms (IQR 86–98 ms), p < 0.001. Compared to males, females had narrower QRS complexes at similar age and similar BMI. In multiple linear regression analysis, BMI correlated positively with QRS duration (standardized beta 0.095, p < 0.001) independent of age, sex, and heart rate. Conclusions: In this large cohort there was a positive association between increasing BMI and QRS duration. Females had narrower QRS duration than males at similar age and similar BMI.